CORRELATION , PATH COEFFICIENTS AND REGRESSION ANALYSIS IN SUMMER SQUASH. - Abdul-Jabbar I. Marie (Mesopotamia Journal of Agriculture)
Simple correlation coefficients were estimated among number of quantitative traits from an experimental data applied by RCB Design with three replications, involved two squash cultivars (Mulla-Ahmed and the hybrid Opal type-HED 103) and four different concentrations of K and IAA (0.0 , 0.5 , 1.0 , 1.5 gl-1) , (0.0 , 100 , 200 , 300 mgl-1) respectively. In order to determine the best traits affecting on the yield, path coefficient analysis was used to divide the correlation coefficients of the yield with its components into direct and indirect effects. To determine the nature response of the different traits for both K and IAA, trend analysis was applied, in which mean squares were divided in a variance analysis table into linear, quadratic and cubic relationship. Significant correlation coefficients in a positive direction were obtained between the total yield and its contributing characters viz. (no . of female flowers , sex ratio , no. of fruits plant -1 , fruit weight and early yield). Number of fruits plant -1 was characterized with highest direct effect on the total yield , whereas, the highest indirect effects resulted from no. of fruits through fruit weight and from no. of female flowers through the path of no. of fruits plant -1. Trend analysis revealed a significant quadratic order regression form between K concentrations with plant height and fruit weight , while the relation between IAA concentrations with no. of branches and early yield showed a significant effect at the second order equation form.